Single-mode lasing from a single 7 nm thick monolayer of colloidal quantum wells in a monolithic microcavity - Foroutan-Barenji, Sina (2021)
In this work, monolithically‐fabricated vertical cavity surface emitting lasers (VCSELs) of densely‐packed, orientation‐controlled, atomically flat colloidal quantum wells (CQWs) using a self‐assembly method is reported and single‐mode lasing from a record thin colloidal gain medium with a film thickness of 7 nm under femtosecond optical excitation is demonstrated. Specially engineered CQWs are used to demonstrate these hybrid CQW‐VCSELs consisting of only a few layers to a single monolayer of CQWs and are achieved the lasing from these thin gain media by thoroughly modeling and implementing a vertical cavity consisting of distributed Bragg reflectors with an additional dielectric layer for mode tuning. Accurate spectral and spatial alignment of the cavity mode with the CQW films is secured with the help of full electromagnetic computations. While overcoming the long‐pending problem of limited electrical conductivity in thicker colloidal films, such ultrathin colloidal gain media can be helpful to enable fully electrically‐driven colloidal lasers.